The relationships between stress, stress-coping behaviors, and suicidal risk among Thais who had become unemployed due to the COVID-19 pandemic: A cross-sectional study - Chalermpon Kajai; Wanich Suksatan; Nittaya Promkunta; Natakorn Kamkaew (Belitung Nursing Journal, 2022)
Background: The COVID-19 pandemic has resulted in severe mental health problems worldwide. Thus, in addition to the high number of people who have died from infection with complications, some have committed suicide.